Protective Mechanism of Luteinizing Hormone and Follicle-Stimulating Hormone Against Nicotine-Induced Damage of Mouse Early Folliculogenesis - Liu, Wen-Xiang; Zhang, Yan-Jie; Wang, Yu-Feng; Klinger, Francesca Gioia; Tan, Shao-Jing; Farini, Donatella; De Felici, Massimo; Shen, Wei; Cheng, Shun-Feng (Frontiers in Cell and Developmental Biology, 2021)
Previous studies have shown that nicotine could impair the germ cell cyst breakdown and the primordial follicle assembly by autophagy. In this paper, we discovered that luteinizing hormone (LH) and follicle-stimulating hormone (FSH) could counteract the damage caused by nicotine of mouse germ cell cyst breakdown. The neonatal mice were separately intraperitoneally injected with nicotine, nicotine plus LH, nicotine plus FSH, and saline (control) for 4 days. Compared with the nicotine group, the quality of oocytes and the number of follicles were remarkably increased in the nicotine plus LH group or nicotine plus FSH group. LH and FSH could alleviate nicotine-induced oocyte autophagy by different pathways. LH reduced the nicotine-induced autophagy by restoring the phosphorylation level of adenosine 5′-monophosphate-activated protein kinase α-1, while FSH by downregulating the phosphorylation level of Forkhead box class O 1. In addition, in a subsequent study of 6-week mice in different treated groups, we found that LH and FSH supplementation significantly improved normal maturation rates, fertilization rates, and embryo’s developmental potential of oocytes in oocytes exposed to nicotine. Taken together, these results suggested that LH and FSH could counteract the damage caused by nicotine and finally ensure normal germ cell cyst breakdown and early embryo development.